Training on Making Eco Enzyme Solutions to Reduce Organic Waste in Sipayo Village - Ria Megasari; Asmuliani R; Irwan Nooyo; Muhammad Nasrul; Muh. Arsyad; Yulan Ismail (Fakultas Sains Dan Teknologi, Universitas Muhammadiyah Sidenreng Rappang, 2025)
Training on making eco enzymes is a strategic step to overcome the problem of organic waste in Sipayo Village. Eco enzyme, the result of fermenting organic waste with sugar and water, has various benefits, including as a natural cleaner, liquid fertilizer, and pest control agent. This program aims to increase public awareness of the importance of managing organic waste while empowering them to create products with high utility value.Training activities involve educational processes, direct practice and mentoring involving various community groups, from housewives to village youth. The evaluation results showed that the participants understood the techniques for making eco enzyme and its benefits. Apart from that, this training also has a positive impact on reducing the volume of organic waste in the village, improving environmental cleanliness, and opening up eco enzyme-based business opportunities. Through this participatory approach, it is hoped that Sipayo Village can become an example of effective and sustainable organic waste management. Training on making eco enzymes not only solves environmental problems, but also strengthens collective awareness of the importance of protecting village ecosystems holistically.